Implementing Innovative Pedagogy and a Rainbow Curriculum to Expand Learning on Diversity - Steven W. Sumner; Sandra Sgoutas-Emch; Lisa Nunn; Evelyn Kirkley (Park University, 2017)
A mixed methods approach analysis examines the impact of incorporating diversity education focusing on sexual diversity at an independent, Roman Catholic university, a site where Lesbian, Gay, Bisexual, Transgender, Questioning/Queer (LGBTQ) individuals face discrimination, harassment, and homophobia. The analysis demonstrates the positive impact of incorporating the sexual diversity education implemented in a cluster-course approach using common learning experiences and outcomes. In comparison to the beginning of the semester, by the end of the semester students were better able to articulate and implement culturally sensitive language, express an understanding of marginalization of sexual minorities as well as discuss heterosexual privilege.